Experimental study of granular flow transition near the outlet in a flat-bottomed silo. (February 2021) - Xiao, Yawen; Han, Yanlong; Jia, Fuguo; Liu, Hanru; Li, Gengrun; Chen, Peiyu; Meng, Xiangyi; Bai, Shigang
Abstract : The discharging process is ubiquitous in the production of food and pharmaceuticals. Usually, discharging devices have relatively simple structures. But unlike the outflow of liquids, due to the transitions in granular flow it is considered a discontinuous process and there is not yet a complete theoretical framework that describes granular outflow from an orifice. In this work, the transition of granular kinematic states near to the outlet is examined experimentally. The transition boundary of a kinematic discontinuity was not found in the study, but there was a transition boundary of velocity profile including velocity gradient transition and motion direction transition near to the outlet. Furthermore, two methods to determinate the transition boundary of velocity profile were developed. This work further clarifies the mechanism and position of flow transition near the outlet during the discharge of grains. This can not only help to solve problems in the discharging process, but also help to enhance our understanding of complex flow properties of granular solids confined by a bottleneck. Graphical abstract: Image 1 Highlights: General rule of kinematics during silo discharging examined experimentally. New insights for the kinematics transition of grain outflow proposed. Two methods developed to identify regions of flow transition. Transition region presents the parabolic arch with height similar to the outlet radius.